Neglected Clubfoot; Surgical Treatment Algorithm Evaluation in Tertiary Care Hospital of Pakistan - Muhammad Arsalan, Muhammad Nadeem Kashmiri, Zahir Khan, Sultan Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The 1 in every 1000 infants are affected by the idiopathic club-foot. It is most commonly observed among the people living in the low middle income countries. Objective: The study was carried out to evaluate the surgical treatment algorithm in case of neglected clubfoot among patients admitted at tertiary care unit. Study design: It is a cohort based retrospective study conducted for the duration of six months from January 2022 to June 2022. Material and Methods: The study was conducted on the 40 patients presented with clubfoot at the tertiary health unit, Khyber Teaching Hospital, Peshawar, were included. The patients mean age was 11 years. The range of patient’s age was from 3 to 25 years. 13 patients went through bilateral intervention. And among these 40 patients there were 15 had received unilateral intervention for each foot. The basic features of the patients were recorded. There were 3 groups made containing operated clubfeet patients, first group included 15 patients, second and third group included 12 patients each. Results: There were 29 patients that received only one follow-up visit. The patients visited their doctors for the first year after surgery but then the visiting attendance became irregular afterwards. The altered ICFSG data was compared for only those patients that completed at least three follow-up visits. The variation between the score of participants between group 1 and 2 was not significant statitically. Conclusion: In case of neglected club-foot condition, PMR has shown excellent to fair results in patients especially children. Therefore, it can be proposed that PMR can be used to lessen the burden of neglected club-foot in the LMICs as it also has no side effects. There is a strong link between age and the surgical outcomes so the treatment must be done as soon as possible. Keywords: Club-foot, PMR, ICFSG data, surgical outcomes.